Introduction to computation and programming using Python : with application to computational modeling and understanding data - Guttag, John (Cambridge, Massachusetts : The MIT Press, 2021)
"Introduces students with little or no programming experience to computational problem solving using Python and various Python libraries"--
Includes index.
CSE
Keywords: Python (Computer program language) -- Textbooks; Computer programming -- Textbooks; Computer science